Effect of 50 MeV Li+3 and 80 MeV C+5 ions' beam irradiation on the optical, structural, chemical and surface topographic properties of PMMA films*. Issue 9 (3rd October 2017) - Bharti, Madhu Lata; Dutt, Sanjay; Joshi, Veena
ABSTRACT: The self-standing films of polymethyl methacrylate (PMMA) were irradiated under vacuum with 50 MeV lithium (Li 3+ ) and 80 MeV carbon (C 5+ ) ions to the fluences of 3 × 10 14, 1 × 10 15, 1 × 10 16 and 1 × 10 17 ions µm −2 . The pristine and irradiated samples of PMMA films were studied by using ultraviolet–visible (UV–Vis) spectrophotometry, Fourier transform infrared, X-ray diffractrometer and atomic force microscopy. With increasing ion fluence of swift heavy ion (SHI), PMMA suffers degradation, UV–Vis spectra show a shift in the absorption band from the UV towards visible, attributing the formation of the modified system of bonds. E g and E a decrease with increasing ion fluence. The size of crystallite and crystallinity percentage decreases with increasing ion fluence. With SHI irradiation, the intensity of IR bands and characteristic bands of different functional groups are found to shift drastically. The change in ( E g ) and ( N ) in carbon cluster is calculated. Shifting of the absorption band from the UV towards visible along with optical activity and as a result of irradiation, some defects are created in the polymer causing the formation of conjugated bonds and carbon clusters in the polymer, which in turn lead to the modification in optical properties that could be useful in the fabrication of optoelectronic devices, gas sensing, electromagnetic shielding and drug delivery.